BMT305 – Microbial Physiology (Fisiologi Mikrob) - PPSKJ, Pusat Pengajian Sains Kajihayat (Pusat Pengajian Sains Kajihayat, 2024)
Second Semester Examination 2023/2024 Academic Session July/August 2024 BMT305 – Microbial Physiology (Fisiologi Mikrob) Duration : 2 hours (Masa : 2 jam)